Electromagnetic and acoustic emission of crystals with proton conductivity; Korus 99; The 3th Russia-Korean International Symposium on Science and Technology; Vol. 2: Proceedings - Zavertkin S. D. Sergey Dmitrievich (1999, 1999)
The radiofrequency electromagnetic impulse emission (REMI) effect under thermal influence upon defected dielectrics has been studied by the authors with thermostimulated acoustic (AE) and radiofrequency electromagnetic emission (TSREE) synchronous registration method and is considered as a new channel of solid body energetic relaxation.